Phenotypic features of CRB1-associated early-onset severe retinal dystrophy and the different molecular approaches to identifying the disease-causing variants - Kousal, Bohdan; Dudakova, Lubica; Gaillyova, Renata; Hejtmankova, Michaela; Diblik, Pavel; Michaelides, Michel; Liskova, Petra (Graefe's archive for clinical and experimental ophthalmology, 2016)
PURPOSE: The aim of this study was to determine the molecular genetic basis of an early-onset severe retinal dystrophy in three unrelated consecutive patients of Czech origin and to describe their ocular phenotype. METHODS: DNA samples from two probands were analyzed using a genotyping microarray (Asper) followed by either target analysis of 43 genes implicated in retinal disorders by next generation sequencing or whole-exome sequencing, respectively. The third proband underwent conventional Sanger sequencing of CRB1 based on her ocular findings. RESULTS: All three probands harboured a known disease-causing mutation c.2843G>A; p.(Cys948Tyr) in the CRB1 gene. One individual was homozygous for this mutation, while in the other two probands c.2308G>A; p.(Gly770Ser) and c.3121A>G; p.(Met1041Val) were also identified in the heterozygous state, respectively. Both variants were novel and evaluated by in silico analysis as pathogenic. A false-negative result was observed in one of the two samples examined by the genotyping microarray. Disease onset in all patients was before the age of 7 years. Hypermetropic refractive error, bilateral nummular retinal pigmentation, retinal thickening and cystoid spaces in the macula were observed in two probands, aged 6 and 7 years. The third proband, aged 28 years, had bone spicule-like pigmentary changes associated with increased retinal nerve fiber layer. CONCLUSIONS: The first study reporting on the molecular genetic cause of non-syndromic early-onset severe retinal dystrophy in Czech patients identified one homozygous and two compound heterozygote probands with CRB1 mutations. Retina nerve fibre layer measurements should be considered an integral part of the clinical evaluation of retinal dystrophies. Detailed clinical examination and imaging can both direct molecular screening and help to confirm or refute disease causation of identified variants.
Keywords: Membrane Proteins; proteiny nervové tkáně; Humans; Eye Diseases, Hereditary; Nerve Tissue Proteins; dítě; Homozygote; mutační analýza DNA; Child; elektroretinografie; Female; mutace; mladý dospělý; dospělí; Phenotype; Genotype; lidé; Retinal Dystrophies; retina; Retina; dědičné nemoci očí; homozygot; Adult; DNA Mutational Analysis; Pedigree; rodokmen; retinální dystrofie; ženské pohlaví; Male; Electroretinography; fenotyp; oční proteiny; Adolescent; Eye Proteins; Young Adult; membránové proteiny; genotyp; Mutation; mužské pohlaví; mladiství